Susceptibility to endemic Aedes‐borne viruses among pregnant women in Risaralda, Colombia. (September 2022) - Cardona-Ospina, Jaime A.; Trujillo, Adriana M.; Jiménez-Posada, Erika V.; Sepúlveda-Arias, Juan C.; Tabares-Villa, Fredy A.; Altieri-Rivera, Joanne S.; Monsalve, Alejandro; Restrepo-Chica, Juliana; Osorio, Daniela; Espinoza, Daniel; Zhu, Yerun; Castrillón-Spitia, Juan D.; et al.
Highlights: Risaralda, Colombia is endemic for Aedes -borne viruses (ABV) like Dengue virus, Zika virus, and Chikungunya virus. ABV transmission is heterogenous, and future work may identify risk factors. Most pregnant women in Risaralda are susceptible to Zika infection. Cord blood is a convenient and efficient sample to achieve public health objectives. Abstract: Objectives: Aedes -borne viruses (ABV) affect humans on every inhabited continent and frequently cause epidemics. Recent epidemics of chikungunya and Zika viruses (ZIKV) highlight that preparedness for future epidemics requires assessment of susceptibility, particularly among high-risk groups. We sought to determine immunity against the three major circulating ABV among pregnant women in an ABV-endemic area of Colombia. Methods: A cross-sectional seroprevalence study was performed, enrolling women presenting to Labor and Delivery. Cord blood and maternal peripheral blood samples were obtained. IgG seroprevalence to flaviviruses and chikungunya was determined by ELISA. An abbreviated neutralization test was used to estimate the frequency and magnitude of immunity to Zika and four dengue serotypes. Cluster analyses explored epidemiologic factors associated with seroprevalence. Results: Most women exhibited high levels of neutralizing antibodies to one or more ABV; however, nearly 20% were seronegative for flaviviruses. Our research took place after the epidemic peak of the ZIKV outbreak in Colombia in 2016. However, only 20% of pregnant women had high levels of Zika-neutralizing antibodies consistent with likely protective immunity to ZIKV. Conclusion: Hence, a high proportion of pregnant women in Risaralda remain susceptible to one or more ABV including the teratogenic ZIKV, indicating a risk for future epidemics in this region.